(untitled) (Journal of Computational Mathematics, 2001)
We present two iterative algorithms, so called SCP and SA respectively, for solving quasicomplementarity problem (QCP). Algorithm SCP is to approximate QCP by a sequence of ordinary complementarity problems (CP). SA is a Schwarz algorithm which can be implemented parallelly. We prove the algorithms above are monotonically convergent.